Accounting in emerging economies - Tsamenyi, Mathew; Uddin, Shahzad (Research in accounting in emerging economies ;, 2009)
Accounting research in emerging economies has grown over the last two decades. This is partly due to the increasing realisation that accounting has a central role to play in the development of these economies. Accounting can contribute to enterprise development, governance improvements and promote foreign direct investment. In addition, the increasing integration of the world economy has led to a significant interest in understanding accounting systems in emerging economies. The articles in the volume contribute immensely to our understanding of how accounting functions in emerging economies. The papers have examined various issues including the adoption of International Financial Reporting Standards (IFRS), internet financial reporting, the impacts of ownership concentration and board characteristics on firm performance, governance practices of firms, corporate social responsibility and environmental accounting, related party transactions, budgetary practices, activity-based costing, and females and the accounting profession. The papers have provided wide ranging empirical and theoretical issues that will have policy implications and also generate future academic debates. Overall, the volume advances debate on the role of accounting in different forms of organisations in emerging economies. We believe the audience will find the papers interesting and insightful in terms of theoretical development, practices, policy implications and future research directions.